<g class="gr_ gr_3 gr-alert gr_spell gr_inline_cards gr_run_anim ContextualSpelling ins-del multiReplace" id="3" data-gr-id="3">Magnetogel Nanospheres Composed of Cisplatin-Loaded Alginate/BCyclodextrin as Controlled Release Drug Delivery - Ali Darini; Touba Eslaminejad; Seyed Noroddin Nematollahi Mahani; Mehdi Ansari (Tabriz University of Medical Sciences, 2019)
Purpose: The main aim of the present study was to design, fabrication and physicochemical characteristics of the magnetogel nanospheres as carriers for Cisplatin in the in vitro environment. Methods: Magnetic nanospheres were synthesized by using a chemical co-precipitation method and coated by sodium alginate through double emulsion method. Then cisplatin was encapsulated into β-cyclodextrin -sodium alginate grafted magnetic nanospheres. The physicochemical properties of the sodium alginate grafted magnetic nanospheres were characterized by using FTIR, particle size analyzing, vibrating sample magnetometry, thermogravimetric and SEM analysis. Also the drug entrapment efficiency, content and in vitro release profile were investigated. Results: Size distribution results revealed that the particles size was distributed in the range of 50± nm. Also morphological properties showed that particles are separated and spherical with the grafted layers of the polymer. The release profile data were in the acceptable range compared to the blank (cisplatin solution). Conclusion: It could be concluded that the sodium alginate grafted magnetic nanospheres could act as a slow and controlled release system to deliver cisplatin.